The Influence Analysis of Brand Trust and Product Quality on Wardah Customer Loyalty - Nur Sa’aadah; Imanuddin Hasbi (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
Changes in lifestyle and the rapid development of the cosmetic industry have caused consumers to become more selective in determining the brand or product to be used. However, the main thing that triggers consumer loyalty to Wardah is still dominated by halal labels. The number of new brands emerging and the decline in index value signifies that Wardah must increase customer loyalty. According to research, several factors influencing consumer loyalty are brand trust and product quality. This study is a research with a quantitative approach, this study uses descriptive data analysis techniques and multiple linear regression analysis, with the number of samples used as many as 100 respondents, the sampling technique used is non-probability sampling. This study indicates that based on the multiple linear regression analysis techniques, it is known that, partially, the brand trust variable (X1) does not affect the consumer loyalty variable (Y). With the same analysis technique, it is known that the product quality variable (X2) significantly influences consumer loyalty (Y). Simultaneously, the variables brand trust (X1) and product quality (X2) significantly affect consumer loyalty (Y)